Las novelas de Arnaldo Alberti - Espinosa Carbonell, Joaquín (Revista de la Sociedad Española de Italianistas, 2009)
RESUMEN: Arnaldo Alberti ha publicado cuatro novelas en italiano hasta el año 2005, con las que ha demostrado tener bien aprendidas dos lecciones literarias: la realista y la decadentista, así como sus dos personajes prototípicos: el vencido y el inepto. En la primera, mezcla de historia e invención, se narra una reunificación familiar. En la segunda leemos la historia de un utópico liberal, Paolo, que acaba con la muerte casual del protagonista. La tercera tiene una interesante trama policíaco-onírica. La cuarta se ambienta en una reunión habida en Brissago en 1925 a la que asistió el Duce. ABSTRACT: Arnaldo Alberti published four novels in Italian before 2005. With these novels he demonstrated his taste for two literary trends: realism and decadentism. He has also developed his two prototypical characters: the defeated and the inept. In his first novel he merges history with fiction, by telling the story of a family reunited. In the second one we can read the story of a liberal utopian named Paolo, which ends up with the accidental death of the main character. The third one has got an interesting police-oneiric plot. The fourth novel is set in a meeting taking place in Brissago in 1925, which was attended by the Duce.